2012
DOI: 10.1111/j.1365-313x.2012.04946.x
|View full text |Cite
|
Sign up to set email alerts
|

The SAUR19 subfamily of SMALL AUXIN UP RNA genes promote cell expansion

Abstract: SUMMARY The plant hormone auxin controls numerous aspects of plant growth and development by regulating the expression of hundreds of genes. SMALL AUXIN UP RNA (SAUR) genes comprise the largest family of auxin-responsive genes, but their function is unknown. Although prior studies have correlated the expression of some SAUR genes with auxin-mediated cell expansion, genetic evidence implicating SAURs in cell expansion has not been reported. The Arabidopsis SAUR19, SAUR20, SAUR21, SAUR22, SAUR23, and SAUR24 (SAU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
383
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 381 publications
(428 citation statements)
references
References 59 publications
17
383
1
5
Order By: Relevance
“…Interestingly, the hypocotyl of these mutants was undistinguishable from the wild type in high R/FR, while in low R/FR, it was slightly but significantly shorter (Supplemental Figure 4I). This finding is consistent with the positive role of SAURs in elongation growth (Spartz et al, 2012(Spartz et al, , 2014. Finally, to test whether both the YUC-dependent and independent responses required the PIFs, we analyzed the expression of IAA1 and SAUR22 in pif4 pif5 pif7 hypocotyls and cotyledons and found that low R/FR induction of these genes was strongly attenuated in the pif triple mutant (Supplemental Figures 4J and 4K).…”
Section: Shade-regulated Expression Of a Subset Of Auxinresponsive Gesupporting
confidence: 56%
See 1 more Smart Citation
“…Interestingly, the hypocotyl of these mutants was undistinguishable from the wild type in high R/FR, while in low R/FR, it was slightly but significantly shorter (Supplemental Figure 4I). This finding is consistent with the positive role of SAURs in elongation growth (Spartz et al, 2012(Spartz et al, , 2014. Finally, to test whether both the YUC-dependent and independent responses required the PIFs, we analyzed the expression of IAA1 and SAUR22 in pif4 pif5 pif7 hypocotyls and cotyledons and found that low R/FR induction of these genes was strongly attenuated in the pif triple mutant (Supplemental Figures 4J and 4K).…”
Section: Shade-regulated Expression Of a Subset Of Auxinresponsive Gesupporting
confidence: 56%
“…Very rapid and coordinated low R/FR-induced expression of members of the SAUR19 group (SAUR19-24) (Supplemental Figure 4G) was particularly interesting in this context because induction of the tested members still occurred in the pin and yuc mutants (Figure 4). To test their functional involvement in shade-induced hypocotyl elongation, we used an artificial microRNA line with downregulated expression of several members of the SAUR19 group (Spartz et al, 2012). Interestingly, the hypocotyl of these mutants was undistinguishable from the wild type in high R/FR, while in low R/FR, it was slightly but significantly shorter (Supplemental Figure 4I).…”
Section: Shade-regulated Expression Of a Subset Of Auxinresponsive Gementioning
confidence: 99%
“…Of 175 K4-SDRGs that displayed a loss of H3K4me3 marks and decreased gene expression, 13 encoded YUCCA-and SAUR-like genes involved in auxin biosynthesis Stepanova et al, 2011;Won et al, 2011) and response, respectively (Spartz et al, 2012(Spartz et al, , 2014. Auxin synthesis sets in motion major changes in gene expression and physiology (Guilfoyle and Hagen, 2007), and the down-regulation of auxin synthesis and signaling can be considered a primary event in the progression of senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that OsSAUR39 acts as a negative regulator of auxin synthesis and transport; overexpression of this gene in rice (Oryza sativa) confers phenotypes including reductions in lateral root development, yield, and shoot and root lengths (Kant et al, 2009). The addition of an N-terminal GFP or epitope tag dramatically increases the stability of SAUR19 to SAUR24 proteins and their ability to function as positive effectors of cell expansion through the modulation of auxin transport (Spartz et al, 2012). However, the function and underlying mechanisms of many SAUR genes remain unknown.…”
mentioning
confidence: 99%
“…SAUR genes can be readily induced by exogenous auxin (Jain et al, 2006) and have been widely used as auxininducible reporters. Studies have correlated some SAUR genes with auxin-mediated cell expansion based on their temporal and spatial expression and their regulation at the transcriptional, posttranscriptional, and protein levels (Esmon et al, 2006;Spartz et al, 2012). Molecular studies have also demonstrated that many SAUR genes contain a highly conserved downstream (DST) element in their 39 untranslated region (UTR) that contributes to mRNA instability in an auxin-independent manner (Sullivan and Green, 1996;Park et al, 2012).…”
mentioning
confidence: 99%